Fundamental chemical kinetics : an explanatory introduction to the concepts - Wright, Margaret Robson (Woodhead Publishing, 2011)
The unusual approach of this text gives final honours and post-graduate students a clear and explanatory account of one of the "harderi areas of physical chemistry. The author takes care to provide detailed verbal clarification of the concepts and their importance together with full explanations of the mathematical developments. Her explanations are an essential and vital feature of the text, which is scholarly, lucid and well-written with a combination of depth of coverage and clarity which helps students to work through on their own. A clear and explanatory account of one of the more difficult areas of physical chemistryProvides detailed verbal clarification of the concepts and their importance together with full explanations of the mathematical developmentsDiscusses energy transfer, molecular beam studies of reactive scattering and historical developments and modern kinetics, among other topics